A Study on the Impact of Various Motor Fitness Characteristics on Performing Ability in High and Low-Performing Divisional Women Cricket Players - Farjana Akter Boby (CV Rezki Media, 2023)
Background: Motor fitness has a big impact on the cricket performance pyramid. Objectives: The research concentrates on certain motor fitness components to improve playing competency in both high- and low-performing Divisional women cricket players. Methods: For this study, 36 female players were randomly selected as subjects from the Bangladesh Women's National Cricket League held in Sylhet in 2022-23. They ranged in age from 16 to 27 years. Three equal groups of twelve people each were formed from the chosen subjects. Khulna, Sylhet, and Dhaka teams were represented by Group I, Group II, and Group III, respectively. Regular exercises and training were provided to enhance the player's performance in the game. Our research scholar additionally prepared the questionnaires with the help of the literature review. The researcher reported the following motor fitness factors: explosive leg power, speed, agility, and cardiovascular endurance. The generated data were gathered during the competition and statistically evaluated after the competition by applying ANOVA and Post Hoc Test (Tukey HSD). The researcher used the statistical software package SPSS version 26 for data analysis. Results: The results of the study showed that there were significant differences in motor fitness characteristics between high and low-performing Divisional women cricket players. High-performing players had significantly better scores on cardiovascular endurance (p=.000), explosive leg power (p=.013), speed (p=.002), and agility (p=.000) than low-performing players. The Champion Team (Sylhet) of the league was discovered to be more successful than other teams in achieving high-level performance. Conclusion The study concluded that to execute the best gaming plan, playing skill exclusively depends on physical condition and a stress-free mind. The study highlights the importance of motor fitness characteristics in cricket performance. The findings may have implications for developing training programs tailored to improve specific motor fitness characteristics for players at different performance levels.